Natural language processing (NLP) fundamentals - Gonçalves, Bruno (Pearson, 2025)
Natural Language Processing LiveLessons covers the fundamentals and some of the more advanced aspects of Natural Language Processing in a simple and intuitive way, empowering you to add NLP to your toolkit. Using the powerful NLTK package, it gradually moves from the basics of text representation, cleaning, topic detection, regular expressions, and sentiment analysis before moving on to the PyTorch deep learning framework to explore advanced topics such as text classification and sequence-to-sequence models. The transformer architectures underlying large language models (LLMs) like ChatGPT, Claude, and BERT are explored in depth along with some practical applications. After successfully completing these lessons you'll be equipped with a fundamental and practical understanding of the full breadth of Natural Language Processing tools and algorithms.
Online resource; title from title details screen (O'Reilly, viewed April 9, 2025)
Keywords: Natural language processing (Computer science); Traitement automatique des langues naturelles; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet